Future Image as a Factor Adaptation Tofirst-Year Students in Higher Learning Environment Education Institutions - Voitovych, Neonila O.; Dell, Herman (Psychological Prospects Journal, 2017)
The article investigates the problem of psychological adaptation of first-year students to the learning environment in higher educational institutions, as well as what are the underlying personal factors of successful adaptation. We assume that the image of the future, as a complex integral formation that includes the value orientation and the first life plans as planned and expected developments, learned patterns of social behavior, elements of self-esteem, attitudes and emotional attitude to the future, is precisely the determining factor that promotes student choice successful strategy to adapt to the learning environment in higher educational institutions. The image of the future − a structural element of individual psychological time, which is a generic visualization model of its own future, it is the result of anticipation of the future (the short, medium and long run). Typically, the problem of adaptation is broken on the new, unfamiliar to the individual situations that are essential to him and vital. This means that no adaptation, “no adaptation” could very likely lead to mental distress individual state of distress, serious threat to its vital interests. Neadaptovanist manifests itself in a lack of understanding of the situation in this method of action that increases the unfavorable situation of zahrozlyvist. The results of studies that are on the one hand the most common problems of freshmen and degree of success of their adaptation to university. On the other - the content and key characteristics of the image of the future. Analysis of the results shows that the image of the future directly affects the process of goal-setting and associated entities such as dreams, goals, plans and programs vital personality. The future for young people is central and requires active alignment ways of achieving their goals. Reflective individual level at a young age allows a rather detailed description of his imaginary future perspective to understand quite a significant period of time, making it even realistic to imagine the distant future. Successfully adapted freshmen have a much clearer and more structured way of the future vision of further prospects and a busy life in reflexive predicting their own future. Also, they are more professionally oriented. Key words: adaptation, future image, self-life strategy, temporal perspective, psychological age, values.